Financing Management In Developing Educational Institutions (Multi-Site Study At Ma Ma'arif Blitar And Sma NU 1 Gresik) - Al Ghozi, Abdullah; Akhyak, Akhyak; Syafi’i, Asrop; Furqon Wahyudi, M. (International Journal of Educational Research & Social Sciences, 2025)
Education plays a pivotal role in educating the nation's life. As a procedure that will determine the outcome based on the quality of the current infrastructure and facilities, as well as the available budget. The principal of the school, who is in charge of planning instruction, needs to effectively manage the funds that are now available from the community, parents, and the government. The principal must adhere to financial management standards to create facilities and infrastructure with the greatest possible success. Regarding that, the purpose of this study is to determine how to apply financial principles to the development of educational institutions. This research is descriptive qualitative research with a multi-site study design. Interviews, in-depth observation, and documentation were used to gather the data. The data analysis technique employed Miles and Huberman's theory, which involved data reduction, data display, and conclusion drawing. Result of the study: 1) The principle of justice has been implemented as follows: a. Give all potential students equal access to education regardless of the background. b. Assisting disadvantaged students with their investment contributions. c. There is no special treatment for rich or poor students. d. The students are free to select courses that will help them explore their interests and talents 2). The effective application of the efficiency principle was demonstrated by: a. Establishing an annual development team. b. Gathering feedback from all school personnel when drafting RAPBS//M and assembling infrastructure development programs. c. hiring a consultant with development expertise.